2006
DOI: 10.1242/dev.02168
|View full text |Cite
|
Sign up to set email alerts
|

MAP kinase subcellular localization controls both pattern and proliferation in the developingDrosophilawing

Abstract: Mitogen-activated protein kinases (MAPKs) phosphorylate target proteins in both the cytoplasm and nucleus, and a strong correlation exists between the subcellular localization of MAPK and resulting cellular responses. It was thought that MAPK phosphorylation was always followed by rapid nuclear translocation. However, we and others have found that MAPK phosphorylation is not always sufficient for nuclear translocation in vivo. In the developing Drosophila wing, MAPK-mediated signaling is required both for patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
44
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 52 publications
10
44
0
Order By: Relevance
“…In addition to its known role in promoting cell cycle progression, it has been suggested that subcellular localization of ERK regulates distinct cellular responses (Marenda et al, 2006;Chuderland et al, 2008). ERK nuclear shuttling is mediated by a nuclear translocation sequence (NTS) within the kinase insert domain of ERK.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to its known role in promoting cell cycle progression, it has been suggested that subcellular localization of ERK regulates distinct cellular responses (Marenda et al, 2006;Chuderland et al, 2008). ERK nuclear shuttling is mediated by a nuclear translocation sequence (NTS) within the kinase insert domain of ERK.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is that enough pMAPK can translocate into the nucleus in the absence of Msk to perform some functions, but that levels are not sufficient for others. Third, some functions of pMAPK may be via cytoplasmic targets, which do not require nuclear translocation, as is known in the developing wing (Marenda et al, 2006).…”
Section: Msk Is Normally Required For Cell Proliferation and Survivalmentioning
confidence: 99%
“…However, we have been unable to identify Drosophila Pea15 or Sef homologs by BLAST analysis. Another possible mediator of MAPK cytoplasmic hold in Drosophila may be the Drosophila homolog of vertebrate importin 7, Moleskin (Msk), which has been found to bind pMAPK and is involved in its nuclear transport, with reported roles in embryonic and wing development (Lorenzen et al, 2001;Baker et al, 2002;Marenda et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this observation, loss-of-function mutations of the Ras/ERK pathway components result in loss of veins, whereas gain-offunction alleles and/or overexpression of these components induce ectopic vein development (Brunner et al, 1994;Kim et al, 2006;Prober and Edgar, 2000;Sturtevant and Bier, 1995). Additionally, phosphorylated cytoplasmic ERK promotes vein differentiation in the developing wing vein and margin cells during the larval and early pupal stage (Marenda et al, 2006). Thus, Ras/ERK is critical for the control of vein differentiation and proliferation in Drosophila.…”
Section: Introductionmentioning
confidence: 99%